Single Nucleotide Polymorphism Genotyping Using BeadChip Microarrays. (1st July 2013) - Lambert, Gilliam; Tsinajinnie, Darwin; Duggan, David
Abstract: The genotyping of single nucleotide polymorphisms (SNPs) has successfully contributed to the study of complex diseases more than any other technology to date. Genome‐wide association studies (GWAS) using 10, 000s to >1, 000, 000 SNPs have identified 1000s of statistically significant SNPs pertaining to 17 different human disease and trait categories. Post‐GWAS fine‐mapping studies using 10, 000s to 100, 000s SNPs on a microarray have narrowed the region of interest for many of these GWAS findings; in addition, independent signals within the original GWAS region have been identified. Focused content, SNP‐based microarrays such as the human exome, for example, have too been used successfully to identify novel disease associations. Success has come to studies where 100s to 10, 000s (mostly) to >100, 000 samples were genotyped. For the time being, SNP‐based microarrays remain cost‐effective especially when studying large numbers of samples compared to other "genotyping" technologies including next generation sequencing. In this unit, protocols for manual (LIMS‐free), semi‐manual, and automated processing of BeadChip microarrays are presented. Lower throughput studies will find value in the manual and semi‐manual protocols, while all types of studies‐‐‐low‐, medium‐, and high‐throughput‐‐‐will find value in the semi‐manual and automated protocols. Curr. Protoc. Hum. Genet . 78:2.9.1‐2.9.34. © 2013 by John Wiley & Sons, Inc.